Knowledge of Greek and Latin Roots is Related to Reading Comprehension among French-Speaking Sixth Graders - Whissell-Turner, Kathleen; Fejzo, Anila (Canadian Journal of Applied Linguistics, 2021)
By the end of primary school, students are confronted with expository texts known for their high proportion of domain-specific academic vocabulary words. These words usually comprise Greek or Latin roots in their internal structure. Recent findings showed that knowledge of Greek and Latin roots is related to reading comprehension. However, no study has investigated such a relationship in a francophone context. Therefore, the present study sought to measure Greek and Latin roots’ relation to reading comprehension among French 6th graders. To do so, 40 participants were administrated an experimental task on Greek and Latin roots knowledge and a reading comprehension standardized subset test. Variables related to reading comprehension, such as morphological awareness, vocabulary breadth, word reading fluency, oral comprehension, and working memory were also measured. Results showed that knowledge of Greek and Latin roots significantly predicted variation of reading comprehension. This paper discusses scientific and educational implications of this finding.